Haggai, Zechariah, and Malachi: an Introduction and Study Guide : Return and Restoration - Stead, Michael R. (T&T Clarḱ€Ös Study Guides to the Old Testament, 2021)
"Michael R. Stead introduces the books of Haggai, Zechariah, and Malachi in light of the latest biblical scholarship. Over the past four decades, there has been an explosion of interest in the postexilic prophets and their role within the Book of the Twelve, which has coincided with paradigm shifts in biblical studies generally. This study guide integrates insights from both historio-critical and literary approaches to examine the authorship, form, structure, and composition of these texts. In particular, this guide explores how the intertextual connections with other scriptures help to shape their meaning. It includes a concise section-by-section overview that highlights key interpretive issues and guides readers in their approach to the text."--